2014
DOI: 10.4103/1947-489x.210373
|View full text |Cite
|
Sign up to set email alerts
|

Histological effects of permethrin insecticide on the testis of adult wistar rats

Abstract: Permethrin is a common constituent in some household insecticides. This study examined the effects of this chemical on the testicular histology of exposed rats. Fifteen adult male Wistar rats were subgrouped into a control and two treatment groups. The controls were fed on normal rat feeds, whilst the diet of animals in the two treatment groups was mixed with 500 mg/kg and 1000 mg/kg Permethrin respectively. An increase in body weights and organ weights was observed in the animals in both treatment groups. Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…As observed in other animal groups (Yuan et al 2010;Omotoso et al 2014), we expected that insecticides would influence the production of gametes. However, our counting of meiocytes indicated that all the examined individuals from the three experimental groups had normal meiocytes at different stages, most abundantly spermatozoa.…”
Section: Chromosomesmentioning
confidence: 79%
“…As observed in other animal groups (Yuan et al 2010;Omotoso et al 2014), we expected that insecticides would influence the production of gametes. However, our counting of meiocytes indicated that all the examined individuals from the three experimental groups had normal meiocytes at different stages, most abundantly spermatozoa.…”
Section: Chromosomesmentioning
confidence: 79%
“…A very important aspect of many studies on pyrethroids is their effect on the reproductive system and fetal progression, as well as after-effects of the exposure to these substances in earlier stages [ 32 , 33 , 34 ]. The effect of a single dose, orally administered permethrin on pregnancy and fetal growth in animals has been examined [ 5 ].…”
Section: Permethrinmentioning
confidence: 99%
“…According to Omotoso et al [22] animals fed on permethrincontaining feeds exhibited some degree of damage in the general histology of their seminiferous tubules. Permethrin could directly reduce sperm motility in vitro [26].…”
Section: Discussionmentioning
confidence: 99%
“…Zhange et al [21] reported that oral administration of permethrin (35 or 70mg/kg/d) for 6 w* in adult mice, resulted in a decrease in sperm count, sperm motility, plasma and testicular testosterone concentration. Some deteriorating effects of permethrin were also reported that affect the normal architecture of the mammalian testis [22].…”
Section: Introductionmentioning
confidence: 99%